The C.L.C. Commission on Constitution and Structure - Sefton, Larry (Relations industrielles / Industrial Relations, 1968)
The author makes a few general comments about the work of the CLC Commission on Constitution and Structure and about a few of the recommendations which seem to be of most importance in the face of the realities of industrial relations and collective bargaining in the 1960’s.